Influence of Promotions on Sales at The Erafone Store Sumedang - Firmansyah, Gugum Aji; Kurniasih, Nining; Damayanti, Wulan Ariani; Kurniawan, Robi; Supranata, Yogi; Crisca, Rini (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
This study aims to determine the extent of the influence of promotions on sales at Erafone Store Sumedang. The research uses a descriptive method with a sample size of 97 respondents. The data source used is secondary data in the form of sales reports from the last three years, 2020-2023. The results of the study show that the implementation of promotions carried out by Erafone is very good, falling into the